Effects of Verbal and Nonverbal Communication of Affection on Avoidantly Attached Partners' Emotions and Message Receptiveness. (November 2020) - Schrage, Kristina M.; Maxwell, Jessica A.; Impett, Emily A.; Keltner, Dacher; MacDonald, Geoff
Research on adult attachment in romantic relationships has focused on the negative outcomes that avoidantly attached individuals face. The present research uses observational research methods to determine if there are specific ways of communicating affection that might help avoidantly attached people reap similar levels of rewards from affectionate communication as those who are more secure. We combined three samples ( N total = 280 couples, 560 participants) who took turns describing a time they felt strong love for their partner, and coded their expressions for cues of verbal affection (i.e., emotion-laden words) and nonverbal affection (i.e., behavioral expressiveness). Higher levels of the speaker's nonverbal affection were associated with stronger positive emotion and behavioral receptiveness (i.e., appearing engaged) for listeners higher in attachment avoidance. Altogether, we provide evidence that avoidantly attached individuals may experience positive outcomes from affectionate exchanges when the communication style is tailored to their unique needs.